Are intergovernmental grants tactical? The evidence from Russia - Elena Jarocińska (Center for Social and Economic Research (CASE), 2008)
Two hypotheses about the determinants of Russian intergovernmental grants are tested empirically. According to first hypothesis, federal transfers to regions correlate with recent voting behavior of regional electorates. Second hypothesis states that transfers are higher in regions with politically powerful governors. We find a strong confirmation for the first hypothesis and no evidence for the second for years 1995-1998. This result is robust across specifications. Panel data analysis allows us to control for regional fixed effects. However, in years 1999-2001 election variables show no effect on transfers. It appears that in the nineties transfers were used by the incumbent government to enhance its reelection probabilities, while by the end of the century this mechanism was no longer in use as the transfer system has become more transparent and objective.
Keywords: H11; H77; R5; P26; 330; Redistributive politics; intergovernmental grants; Russia; Finanzausgleich; Finanzbeziehungen; Russland